Rate of Return to Investment in Education: A Case Study of Faisalabad - Javed, Zahoor Hussain; Arshad, Nafeesa (Journal of Asian Business Strategy, 2013)
The main aim of this research was to obtain rate of return to investment in education which is based on human capital Theory. This study seeks to find association between experience, education and earnings of university teacher. Therefore, this study is based on primary data which was collected from selected universities of Faisalabad. By using OLS techniques, this study analyzes the data and explores and concludes that experience and raising level of education put positive impact on earnings of university teachers. Furthermore it also describes that male teachers earn more than female teachers in education sector. The findings proved that the return to investment in education for polytechnic diploma program is fairly attractive and socially profitable for 2006.